An Affect of Leadership and Compensation towards Employee Performance: Case of PT Mutu Prima Utama Employees in Jakarta - Vendra Gunawan (International Journal of Management Science and Application, 2024)
This study aims to analyze the magnitude of the affect of leadership and compensation on the performance of PT Mutu Prima Utama employees both partially and together. This research is an explanatory research with a quantitative approach. The sample in the study was 43 respondents with a saturated sample method. Data collection techniques use observation techniques, questionnaires, and literature studies. The data analysis with multiple linear regression. The results showed that leadership and compensation were proven to positively and significantly affect the performance of PT Mutu Prima Utama employees partially or together, as for the impact of the contribution is strong at 54.1 percent.